Application of the "Hanifida" Method as an Effective Strategy for Memorizing Asmaul Husna for Early Childhood - Rodliyah, Ismiyati Umi; Wardhani, Junita Dwi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The purpose of this study was to determine the application of the Hanifida Method as an effective strategy for memorizing Asmaul Husna for early childhood, as well as to identify the supporting and inhibiting factors in the application of the Hanifida Method as an effective strategy for memorizing Asmaul Husna.Methodology: This study used a qualitative descriptive approach. The research was conducted at BA Aisyiyah 02 Grogol in August 2025. The subjects of this study were teachers, the principal, and 24 children in class B. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation.Results: The results of this study show that the application of the Hanifida Method is very helpful for young children in memorization. This is evidenced by the fact that the children at BA Aisyiyah 02 Grogol have memorized 64 Asmaul Husna.